PENGARUH TEKNIK SELF MANAGEMENT UNTUK MENGURANGI PROKRASTINASI AKADEMIK - Fitriani, Melin; Khairun, Deasy Yunika; Handoyo, Alfiandy Warih (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2023)
Abstract: Procrastination is a mechanism for dealing with anxiety related to how individuals start or complete work and how decisions are made. Procrastination carried out at school in connection with academic tasks is called academic procrastination. The phenomenon that occurs in students who often delay doing schoolwork is a problem in itself for teachers and students themselves. The aim of the research is to determine the effect of self-management techniques to reduce academic procrastination. The type of research used is single subject research (SSR) experimental research with 4 students as subjects. The data collection method uses a questionnaire or academic procrastination questionnaire. Data analysis techniques use analysis within conditions and analysis between conditions. The results of the study showed that the overall average percentage reduction for subject 1 and subject 4 from the baseline phase (A1) to the baseline phase (A2) was 33%, while for subject 2 and subject 3 it was 31%. In addition, the overlap data from the baseline A1 phase to the intervention phase, and the intervention phase to the baseline A2 phase has an overlap percentage of 0%, the highest percentage reduction occurs in the A1 baseline phase to the intervention phase by applying four stages, namely: 1) self monitoring, 2 ) positive reinforcement (self reward) 3) agreement with yourself (self contracting) 4) mastery of stimuli (stimulus control), so that self management techniques are quite effective in reducing academic procrastination in class XII Science students at SMA Negeri 4 Pandeglang.Keywords: Self Management Techniques; Academic Procrastination.Abstrak: Prokrastinasi merupakan suatu mekanisme dalam rangka menghadapi kecemasan yang berkaitan dengan bagaimana cara individu memulai atau melengkapi suatu pekerjaan serta cara pengambilan sebuah keputusan. Prokrastinasi dilakukan di sekolah berkaitan dengan tugas-tugas akademik disebut dengan prokrastinasi akademik. Fenomena yang terjadi pada siswa yang sering menunda melakukan tugas sekolah menjadi masalah tersendiri bagi guru dan siswa itu sendiri. Tujuan penelitian adalah mengetahui pengaruh teknik self management untuk mengurangi prokrastinasi akademik. Jenis penelitian yang digunakan yakni penelitian eksperimen single subject research (SSR) dengan subjek berjumlah 4 orang siswa. Metode pengumpulan data menggunakan angket atau kuesioner prokrastinasi akademik. Teknik analisis data menggunakan analisis dalam kondisi dan analisis antar kondisi. Hasil penelitian menunjukkan bahwa persentase penurunan rata-rata keseluruhan untuk subjek 1 dan subjek 4 pada fase baseline (A1) ke fase baseline (A2) sebesar 33%, sedangkan subjek 2 dan subjek 3 sebesar 31%. Selain itu, data overlap pada fase baseline A1 ke fase intervensi, dan fase intervensi ke fase baseline A2 memiliki persentase overlap sebesar 0%, penurunan persentase tertinggi terjadi pada fase baseline A1 ke fase intervensi dengan mengaplikasikan empat tahap yaitu: 1) self monitoring, 2) reinforcement yang positif (self reward) 3) perjanjian dengan diri sendiri (self contracting) 4) penguasaan terhadap rangsangan (stimulus control), sehingga teknik self management cukup efektif dalam mengurangi prokrastinasi akademik siswa kelas XII IPA SMA Negeri 4 Pandeglang.